One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Spontaneous mutations in FgSAD1 suppress the growth defect of the Fgprp4 mutant by affecting tri‐snRNP stability and its docking in Fusarium graminearum - Xiaoping Li; Zhili Fan; Ming Yan; Jia Qu; Jin‐Rong Xu; Qiaojun Jin (Environmental Microbiology, 2019)
Summary FgPrp4, the only kinase in the spliceosome, is not essential for viability, but is important for splicing efficiency in Fusarium graminearum . The Fgprp4 deletion mutant had severe growth defects but often produced spontaneous suppressors with faster growth rate. To better understand the suppression mechanism, we identified and characterized spontaneous mutations in the tri‐snRNP‐specific protein, FgSad1, which suppressed the growth defects of Fgprp4 . The L512P mutation was verified for its suppressive effects on Fgprp4 , suggesting that mutations in FgSad1 may have effects involving FgPrp4 phosphorylation on FgSad1. Phosphoproteomics analysis showed that FgSad1 may not be the direct substrate of FgPrp4 kinase. Furthermore, truncation analysis showed that the N‐terminal, extra RS‐rich region of FgSad1 is critical for its function and is post‐translationally modified. The P258S or S269P mutations in FgSad1 increased its interactions with the U5 protein FgPrp8 and the U4/U6 protein FgPrp31, which may result in tri‐snRNP stabilization. Additionally, the D76N mutation increased the association of FgSad1 with the U2 snRNP. These data indicate that suppressor mutations in FgSad1 increase the stability of the tri‐snRNP and/or the affinity of FgSad1 with U2 snRNP and therefore potentially facilitate the docking of tri‐snRNP into the spliceosome.

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Genetic diversity of 324 cultivated tomato germplasm resources using agronomic traits and InDel markers - Lan Jin; Liping Zhao; Yinlei Wang; Rong Zhou; Liuxia Song; Liping Xu; Xia Cui; Ren Li; Wengui Yu; Tongmin Zhao (Euphytica, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)